Ad valorem platform fees, indirect taxes, and efficient price discrimination. (17th May 2017) - Wang, Zhu; Wright, Julian
Abstract : This article explains why platforms such as Amazon and Visa rely predominantly on ad valorem fees, fees which increase proportionally with transaction prices. It also provides a new explanation for why ad valorem sales taxes are more desirable than specific taxes. The theory rests on the ability of ad valorem fees and taxes to achieve efficient price discrimination, given that the value of a transaction to buyers tends to vary proportionally with the cost of the good traded.